Fitting Love and Uniqueness - He, Xian (Ethical theory and moral practice, 2025)
According to the Quality Account of love, only lovable properties of the beloved person, such as beauty, wisdom and kindness, can make love for that person fitting. The account has been criticized for leading to implausible conclusions. If this account is correct, it would seem fitting to replace one’s lover with someone who possesses the same or more lovable properties, or stop loving someone who has lost these properties. Moreover, it is unclear how the Quality Account can differentiate between the fittingness conditions of love and other similar attitudes which seem also fitting in virtue of the same properties. I propose a new response to these objections. I argue that these challenges can be met by appealing to a distinctive lovable property that all objects of love share: their uniqueness. Uniqueness, along with other lovable properties, determines how worthy of love a person is.